Ultrabroadband on-chip photonics for full-spectrum wireless communications - Zihan Tao; Haoyu Wang; Hanke Feng; Yijun Guo; Bitao Shen; Dan Sun; Yuansheng Tao; Changhao Han; Yandong He; John E. Bowers; Haowen Shu; Cheng Wang; et al. (Nature, 2025)
Abstract The forthcoming sixth-generation and beyond wireless networks are poised to operate across an expansive frequency range—from microwave, millimetre wave to terahertz bands—to support ubiquitous connectivity in diverse application scenarios1–3. This necessitates a one-size-fits-all hardware solution that can be adaptively reconfigured within this wide spectrum to support full-band coverage and dynamic spectrum management4. However, existing electrical or photonic-assisted solutions face a lot of challenges in meeting this demand because of the limited bandwidths of the devices and the intrinsically rigid nature of system architectures5. Here we demonstrate adaptive wireless communications over an unprecedented frequency range spanning over 100 GHz, driven by a thin-film lithium niobate (TFLN) photonic wireless system. Leveraging the Pockels effect and scalability of the TFLN platform, we achieve monolithic integration of essential functional elements, including baseband modulation, broadband wireless–photonic conversion and reconfigurable carrier and local signal generation. Powered by broadband tunable optoelectronic oscillators, our signal sources operate across a record-wide frequency range from 0.5 GHz to 115 GHz with high-frequency stability and consistent coherence. Based on the broadband and reconfigurable integrated photonic solution, we realize full-link wireless communication across nine consecutive bands, achieving record lane speeds of up to 100 Gbps. The real-time reconfigurability further enables adaptive frequency allocation, a crucial ability to ensure enhanced reliability in complex spectrum environments. Our proposed system represents a marked step towards future full-spectrum and omni-scenario wireless networks.